MECHANISM FOR APPLYING FOR CREDIT RELAXATION AT FINANCING INSTITUTIONS IN DENPASAR - Made Aditya Sathya Bhaskara; I Made Dwi Dimas Mahendrayana (Transpublika Publisher, 2023)
This study aims to determine the mechanism of applying for credit relaxation at financing institutions in Denpasar and identify the inhibiting factors in applying for credit relaxation at financing institutions. The method used is empirical, with primary data sources consisting of interviews with respondents and informants, and secondary data sources consisting of library materials such as books, journals, and internet media. The results showed that there is a mechanism for applying for credit relaxation submitted by the debtor to the creditor, which is adjusted to the policies of each financing institution. The factors inhibiting credit relaxation in financing institutions are both internal and external. Internal factors include technological problems, while external factors include frequent interruptions in internet connectivity.